2013
DOI: 10.1242/jeb.094243
|View full text |Cite
|
Sign up to set email alerts
|

Detection and selective avoidance of near ultraviolet radiation by an aquatic annelid: the medicinal leech

Abstract: Medicinal leeches are aquatic predators that inhabit surface waters during daylight and also leave the water where they might be exposed to less screened light. Whereas the leech visual system has been shown to respond to visible light, leeches in the genus Hirudo do not appear to be as negatively phototactic as one might expect in order to avoid potential ultraviolet radiation (UVR)-induced damage. I used high intensity light emitting diodes to test the hypothesis that leeches could detect and specifically av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Little has been known about processing of visual information in the leech, and less about processing of information relating to water movement. It was known, however, that one particular interneuron, the S cell, responds to both visual and mechanical stimuli (Bagnoli et al, 1973;Gardner-Medwin et al, 1973;Kretz et al, 1976;Sahley et al, 1994;Jellies, 2014). By presenting nearly intact leeches with natural water waves in complete darkness, we demonstrated that the S cell responds readily to purely mechanically cued water waves (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Little has been known about processing of visual information in the leech, and less about processing of information relating to water movement. It was known, however, that one particular interneuron, the S cell, responds to both visual and mechanical stimuli (Bagnoli et al, 1973;Gardner-Medwin et al, 1973;Kretz et al, 1976;Sahley et al, 1994;Jellies, 2014). By presenting nearly intact leeches with natural water waves in complete darkness, we demonstrated that the S cell responds readily to purely mechanically cued water waves (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…As mentioned, the vast majority of S cell spikes recorded near the middle of the leech (in segments 10 and 14) traveled in a caudorostral direction (Figs 3D,E and 4A). This may be caused by the same mechanism that causes light flashes onto the tail of a leech to elicit more S cell spikes than light flashes onto the head (Jellies, 2014;Wagenaar and Stowasser, 2016). One possible explanation of these effects could be that posterior sensilla may be more sensitive to light and water motion than the anterior sensilla.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the leech has been the subject of biological investigation for over 100 years, studies performed over the past decade have led to the identification of two newly described behaviors, which I discuss in turn: one is the first social behavior described in the leech (Bisson and Torre, 2011), the other is a newly discovered sensitivity to UV light (Jellies, 2014a).…”
Section: Newly Described Behaviorsmentioning
confidence: 99%
“…However, invertebrate opsins that are sensitive to green light commonly have a substantial secondary sensitivity peak at UV wavelengths (Stavenga, 2010), suggesting that this assumption might be false. Indeed, Jellies (2014a) found that leeches retract or move away from bright UV light (400 nm) projected onto their dorsal surfaces. Such responses were rarely seen to visible light.…”
Section: Novel Responses To Visual Stimulimentioning
confidence: 99%
“…Avoidance behaviours to UV radiation have been shown in a range of aquatic organisms, and include the movements of bacteria (Bebout & Garcia-Pichel 1995), negative phototaxis in zooplankton (Pennington & Emlet 1986, Alonso et al 2004, Hansson et al 2007), movement in leeches (Jellies 2014), settlement in coral larvae (Gleason et al 2006) and covering behaviours of sea urchin (Adams 2001, Verling et al 2002, Dumont et al 2007). …”
Section: Introductionmentioning
confidence: 99%